Penetrating Facial Injury by Motorcycle Gear Shifter Lever: A Case Report - Zulfikar, Welli; Arip Heru Tripana (HM Publisher, 2022)
Background: Penetrating facial injury can cause injury to the bone and soft tissue surrounding. Penetrating facial injury caused by organic foreign bodies or metal material increases the risk of infection in the wound. Identification of the location of the entry of foreign bodies, whether the vital organs, the presence of injury to the nerves, vascular, visual, and other muscle damage is very important to do. For that immediate and optimal treatment can be applied to reduce morbidity and mortality. Case presentation: A 13 years old boy arrived in ER admission with penetrating facial injuries. A corpus alienum penetrated the patient’s face at the medial meatus of the right eye along with bleeding from the nose and around the wound. Evaluation and management of the penetrating facial injury were performed in accordance with the ATLS protocol. The aim of management in penetrating facial injuries is to remove the foreign body with minimal trauma to surrounding structures and to maintain normal function and optimal appearance. The patient underwent emergency surgery the remove corpus alienum and wound exploration under general anesthesia. Postoperative evaluation shows no bleeding or signs of infection, no visual impairment, and tear flow were found. Conclusion: Penetrating facial injury due to motorcycle gear shifter lever is rare. Good Management of penetrating facial injury will give satisfactory results.